New species of the genus Elimaea Stål, 1874 (Tettigoniidae: Phaneropterinae) from China - Wang, Gang; Shi, Fuming (Zootaxa, 2017)
Eight new species of the genus Elimaea are described from China, belonging to subgenera Rhaebelimaea and Poaefoliana, i.e. E. (Rhaebelimaea) acuminata sp. nov., E. (Rh.) expansa sp. nov., E. (Rh.) trapeziformis sp. nov., E. (Rh.) maculata sp. nov., E. (Rh.) mucronatis sp. nov., E. (Rh.) saturata sp. nov., E. (Rh.) elongata sp. nov., and E. (Poaefoliana) emlobata sp. nov. Appropriate photographs and illustrations for new species are provided. The material is deposited in the Museum of Hebei University.